REVIEW ABOUT EFFICIENCY OF PREOPERATIVE AND POSTOPERATIVE PHYSIOTHERAPY TREATMENT ON URINARY INCONTINENCE IN PROSTATECTOMISED MEN - Cuevas-López , J; Cuevas-López , A (Cuestiones de Fisioterapia, 2016)
Introduction: urinary incontinence affects 30 to 50 % of prostatectomised men; and although there are studies on the effect of different physiotherapy modalities in this health problem, the impact of any type of physical therapy in post-prostatectomy urinary incontinence is not well established. Objective: to determine the existence of evidence in the scientific literature on the effectiveness of physiotherapy procedures used in the prevention, or re-solution of urinary incontinence after prostate surgery. Material and method: a review in PubMed, PEDro, MED-LINE, ProQuest, Web of Science, Cuiden, Crochane Plus Library, National Library of Health Sciences and Virtual Health Library BIREME, was performed. Randomized clinical trials published during the last 10 years in English, Spanish or French were included. Sample size applied treatment and number of sessions, measurements, results and significant observations were compared. Results: of the 45 initially articles, 28 were removed. 17 full texts were analyzed, of which 7 were removed, and 10 were included for study. Discussion/Conclusions: pelvic floor exercises and electrical stimulation are key procedures to get an early-stage urinary control.